Produksi Semangka Heterosis dengan Tetua Betina Jantan Mandul Triploid dan Jantan Hibrida Diploid - Badami, Kaswan (Rekayasa, 2008)
Watermelon (Citrullus vulgaris, Schard) is a seasonal fruit playing an important role in economic improvement of a household and a nation as well. An effort to cultivate watermelon greatly supports the improvement offarmers' standard of living. Its Physical appearance and itsflesh color are greatly attractive. It has various stripped shape (elips, round and oval) and has highly enough nutrition.The aims of this stud y were to discover diploid watermelon varieties used as good polinator and has more strengths than both of its parents. This stud y applied Randomized Block Design with two replications treating nine (9) seeded watermelon and two (2) triploid verities. Thevarieties used as male parents were diploid variety (Pl), Diana Bangkok Dragon (P2), China Dragon (P3), Black sweet (P4), Golden Fresh (PS), Hitam manis (p6 ), Grand Master (pl), TM Tiger (PB), and Red Super Dragon (P9). Pretty Orchid (V1) and Champion (V2) were used asfemale parents.The results of this stud y showed that different polinators had different influences in determining the agronomic possibility of bearing fruit, sugar content,fruit length,fruit diameter except harvesting age and fruit weight. The best agronomic properties resulted from well crossing were shown byfruit diameter and sugar content. Withinvariety-crossing of all polinator with thefemale Pretty Orchid (V1) showed good results except the polinator Hitam Manis (p6 ). The greatest fruit diameter resulted from polinator Grand Master (Pl) was 22.59 cm dan the smallest resulted from Hitam Manis polinator (P6) was 20.20 cm